Sistem Saraf Tepi Dan Otonom: Struktur, Interaksi Homeostatik, Dan Implikasi Klinis - Syafrianto Syafrianto; Marhadi Efendi; Ahmad Lahmi; Dasrizal Dahlan; Rosniati Hakim (Nan Tongga Health And Nursing, 2025)
The interaction between the Peripheral Nervous System (PNS) and the Autonomic Nervous System (ANS) plays a crucial role in maintaining the body's homeostasis. This study aims to analyze the cooperative mechanisms between the PNS and ANS in responding to physiological changes such as blood pressure, body temperature, and digestive processes, as well as to evaluate the clinical implications and pathophysiology resulting from dysfunctions in these nervous systems. The research method employed is a qualitative descriptive approach using library research techniques. Data were collected from various scientific literatures, medical textbooks, and indexed articles in databases such as PubMed, ScienceDirect, and Google Scholar. The analysis was conducted using content analysis and source triangulation to ensure data validity. The findings show that the coordination between the PNS and ANS is essential for effectively integrating sensory and motor impulses with the body’s autonomic responses. Disorders such as peripheral neuropathy, autonomic dysreflexia, and dysfunctions due to diabetes mellitus significantly affect an individual's physiological stability. Accurate diagnosis through technologies such as electromyography (EMG) and autonomic function tests is vital for the early management of these conditions. Furthermore, therapeutic approaches involving pharmacological combinations, neurofunctional rehabilitation, and other supportive therapies yield significant outcomes in nerve function recovery. This study concludes that a deep understanding of the interaction between the PNS and ANS is a fundamental basis for developing holistic clinical strategies to maintain neural health and enhance the overall quality of life for patients.